Infection Prevention and Control Preparedness Level and Associated Determinants in 56 Acute Healthcare Facilities in Ghana - Oppong, Timothy Bonney; Amponsem-Boateng, Cecilia; Kumi Duodu Kyere, Emmanuel; Wang, Ying; Gheisari, Zohreh; Ekua Oppong, Eunice; Opolot, Godfrey; Duan, Guangcai; Yang, Haiyan (Infection and drug resistance, 2020)
Infection prevention and control (IPC) is a globally relevant aspect of all health systems impacting the health and safety of both patients and healthcare workers. However, best practices remain a challenge in healthcare delivery especially in resource limited situations. The primary objective of this study was to assess the infection prevention and control (IPC) preparedness levels of acute healthcare facilities in Ghana and to determine the factors associated with the overall IPC preparedness levels in acute healthcare facilities. Methods: A cross-sectional study adapting the IPC assessment framework (IPCAF) developed by the World Health Organization (WHO) was conducted. Five of the core components of the WHO IPCAF were used to assess the IPC level of 56 acute healthcare facilities in Ghana. Results: Of the 56 facilities surveyed, only 19 had an IPC program with clearly defined objectives. Overall, 8 (14.3%) facilities scored an IPC preparedness level of “Advance”, 18 (32.1%) facilities received an “Intermediate” IPC preparedness score, 23 (41.1%) facilities received an IPC preparedness level of “basic” and 7 (12.5%) facilities scored an IPC preparedness level of “inadequate”. IPC materials like detergents, running water and PPEs were not significantly supplied. Government owned facilities performed better in terms of IPC preparedness as compared to privately owned facilities. A PLUM-ordinal regression analysis revealed that an IPC program with clearly defined objectives (OR= 76; 95% CI; 7.23, 808.19), dedicated IPC budget (OR= 13; 95% CI; 3.8–44.3) and regular mandatory training (OR= 50.9; 95% CI; 6.1–425) were associated with increased IPC preparedness. Conclusion: Generally, the IPC preparedness levels in a majority of the facilities were low and required significant improvements in several areas. Facilities must make periodic reviews and adjust their objectives based on facility priorities.
Keywords: Infection prevention and control; Infection prevention preparedness; Assessing infection prevention and control programs; Infection prevention and control policy